Can Prosopis juliflora (Swartz) DC., Withstand Climatic Aberration in Semiarid Regions of Central India? - An Observation from Bundelkhand - Ramesha, M. N.; Adhikary, P. P.; Dwivedi, V. K.; Rathakrishnan, P.; Tiwari, S. P. (Indian Forester, 2015)
This paper discusses the influence of extreme cold on Prosopis juliflora, recorded in Bundelkhand region at Datia, Madhya Pradesh, in the year 2011. P. Juliflora more akin to Australian form has colonised on the parched tank bed since 2004 and it has grown lavishly. P. juliflora die-back was observed in low lying area of about 5ha on the parched tank bed. Complete die-back (up to 93 % of stems over almost five hectare) was observed in second fort night of January 2011. Its 0 0 die-back has been attributed to extreme low temperature recorded as-1.5 C to 3 C during first 12 days of January 2011. Low lying areas with high soil moisture content coupled with high stand density and low temperature prevailing for a considerable period might be the reason for freezing of available soil moisture to the plants and causing die-back. Plants have started recuperating by sprouting new shoots in main stem and at base since first week of March 2011. No die-back symptoms were observed in plants grown at higher elevation in the adjoining area.